Why It Won’t Displace Police Analysts Artificial Intelligence - Muhammad Faizal Bin Abdul Rahman (2017)
Any concerns over Artificial Intelligence (AI) replacing law enforcement intelligence analysts are presently unfounded. Rather, AI and analysts would share a symbiotic working relationship.